Takayasu Associated Myocarditis in a Young Female: A Case Report - Mahdieh Aghababaie; Razieh omidvar; Hamidreza Pouraliakbar; Babak Mohammadi todeshki; Simin Almasi (Journal of Cardio-Thoracic Medicine, 2023)
Takayasu arteritis (TA) is a rare granulomatous panarthritis, characterized by stenosis or obliteration of large and medium-sized arteries, such as the aorta. The onset of symptoms tends to lead to a delay in diagnosis that can range from months to years, during which time vascular disease may initiate and progress to become symptomatic. In this context, TA may present with various uncommon cardiovascular complications such as dilated cardiomyopathy, valvulitis, and myocarditis. Herein, we report on a 29-year-old female who initially presented with active myocarditis and was later incidentally diagnosed with TA.